Theory of highly loaded coal-water slurries - Biletskyi, V. S.; Krut, O. A.; Sergeyev, P. V. (Криворізький національний університет, 2014)
There has been analyzed the existing schemes of strapping of circulated system of drilling set during drilling with well washing by the foam and argued the necessity of its efficient raising; there has been chosen the scheme of strapping of circulated system during drilling with well washing by the foam for the possibility of the most rational usage of existing foamgenerating equipment.

В статті проаналізовані існуючі схеми обв'язки циркуляційної системи бурової установки при бурінні з промиванням свердловини піною та обґрунтована необхідність підвищення їх ефективності; для можливості найбільш раціонального використання існуючого піногенеруючого устаткування передбачена схема обв'язки циркуляційної системи при бурінні з промиванням свердловини піною.